Combined effects of sorption hysteresis and its temperature dependency on wood materials and building enclosures – Part I: Measurements for model validation. (September 2016) - Zhang, Xiaobo; Zillig, Wolfgang; Künzel, Hartwig M.; Mitterer, Christoph; Zhang, Xu
Abstract: Hygroscopic materials such as wood and wood based materials have been widely used as insulation and surface moisture buffering materials due to their low thermal conductivity and high moisture capacity. And their hygrothermal performance is mainly dependent on the moisture properties, such as sorption isotherm and water vapor permeability etc. Instead of a univalued function of relative humidity, sorption isotherm of wood materials is not only affected by sorption history, but also temperature dependent. A heat and moisture transport model is formulated based on local thermodynamic equilibrium assumption, which includes thermal moisture capacity and a hysteresis model in [1]. To validate this model, sorption isotherms at 23 °C were measured using the static gravimetric method; and a moisture response test under dynamic boundary conditions was carried out in a climatic chamber. The simulation results show that the hygrothermal model with temperature dependency and sorption hysteresis can capture the dynamic moisture response to variable boundary conditions very well. Therefore, this model could be used to further analyze the individual and combined effects of sorption hysteresis and its temperature dependency through hygrothermal modeling in a companion paper. Highlights: Sorption isotherms and four primary desorption scanning curves of spruce were measured at 23 °C. A dynamic moisture response test was measured in a climatic chamber. A hygrothermal model with temperature dependent sorption hysteresis was validated.